Enrichment of Triglyceride-Rich Lipoproteins with Apolipoprotein C-I Is Positively Associated with Their Delayed Plasma Clearance Independently of Other Transferable Apolipoproteins in Postmenopausal Overweight and Obese Women. Issue 5 (29th March 2017) - Wassef, Hanny; Bissonnette, Simon; Dufour, Robert; Davignon, Jean; Faraj, May
Abstract: Background: The role of plasma apolipoprotein (apo) C-I in cardiometabolic risk in humans is unclear. However, in vitro studies showed a dual role for apoC-I, both protective and harmful, depending on the carrier lipoprotein. Objective: We tested the hypothesis that triglyceride (TG)-rich lipoprotein (TRL) apoC-I, not total or HDL apoC-I, is associated with delayed postprandial plasma clearance of TRLs, independently of apoC-II, apoC-III, and apoE. Methods: This cross-sectional study examines the plasma clearance of a 13 C-triolein–labeled high-fat meal (68% fat energy) in 20 postmenopausal overweight and obese women [body mass index (in kg/m 2 ) ≥27; aged 45–74 y] as the increment change in area under the 6-h postprandial curves (iAUC6h ) of TRL parameters. Lipoproteins were fractionated by fast-protein LC. Transferable apolipoproteins were measured by ELISA. TRL enrichment with apolipoproteins was calculated by dividing their TRL concentrations by TRL apoB. The effects of human apoC-I and apoC-III on the hydrolysis and storage of 3 H-triolein–labeled TRLs were tested in 3T3-L1 adipocytes. Results: TRL apoC-I was positively associated with plasma apo B-48 and total and non-HDL TGs, cholesterol, and apoB ( r = 0.52–0.97) and negatively with HDL cholesterol ( r = −0.52) and LDL diameter ( r = −0.91) ( P < 0.05). Total and HDL apoC-I were correlated only with total ( r = 0.62) and HDL ( r = 0.75) cholesterol. Women with high fasting TRL enrichment with apoC-I (99–365 μmol apoC-I/μmol apoB), but not apoC-II, apoC-III, or apoE, had higher iAUC6h for TGs (+195%), 13 C-TGs (+319%), and apo B-48 (+186%) than those with low enrichment (14–97 μmol apoC-I/μmol apoB). The 4-h postprandial increase in TRL apoC-I was associated with a 4-h increase in TRL TGs and iAUC6h for TGs, 13 C-TGs, and apo B-48 ( r = 0.74–0.86, P < 0.001), independently of 4-h changes in TRL apoB, apoC-II, apoC-III, or apoE. ApoC-I and apoC-III inhibited 3 H-TRL clearance by adipocytes by >75% ( P < 0.001). Conclusions: TRL enrichment with apoC-I is positively associated with postprandial hypertriglyceridemia and remnant accumulation in postmenopausal overweight and obese women, independently of apoC-II, apoC-III, or apoE, which may be due to inhibiting TRL clearance by adipocytes. Reducing TRL apoC-I may ameliorate delayed postprandial plasma clearance of TRLs and associated risks in humans.